OPTIMAL POLICY FOR PORT SUPPLY CHAIN ORIENTATION AS A STEP TO IMPROVE THE PERFORMANCE OF THE NIGERIAN INDUSTRIAL SECTOR - ONI, BABATOPE GABRIEL; OLUWAKOYA, O. ADENIYI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The study evaluates Apapa and Tin Can Ports’ industrial sector orientation to evaluate the food and beverage supply chain in Lagos and Ogun states, proposing solutions. The port supply chain orientation was assessed using port throughput (PT), while industrial performance was evaluated using manufacturing production value (MPV). The Nigerian Port Authority (NPA) provided data on port throughput for eight years from 2014 to 2021. The Manufacturers Association of Nigeria (MAN) provided data on manufacturing production values. Multiple regression analyses reveal a significant and direct relationship between the MPV of the food and beverage sector and the PTs of Apapa and Tin-can Island ports. The effects of PT on MPV vary across seaports, with Tin Can Port PT having a greater impact than Apapa PT. The research reveals variations in the impact of port supply chain orientation across different manufacturing clusters (Apapa, Ikeja, Ogun) at the cluster level. The cluster-specific analysis enhances the understanding of the findings and enables the development of personalized policy recommendations.